Third IEEE International Conference on Data Mining 2003
DOI: 10.1109/icdm.2003.1250987
|View full text |Cite
|
Sign up to set email alerts
|

Learning rules for anomaly detection of hostile network traffic

Abstract: We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(77 citation statements)
references
References 7 publications
0
77
0
Order By: Relevance
“…Just the same as Mahoney et al, We refer to them as NETAD-C and LERAD-C respectively. Therefore, we compare the performance of LERAD-GP with that of the other two algorithms, which are tested in both modified DARPA 1999 and the mixed dataset in [4]. The results are as follows.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Just the same as Mahoney et al, We refer to them as NETAD-C and LERAD-C respectively. Therefore, we compare the performance of LERAD-GP with that of the other two algorithms, which are tested in both modified DARPA 1999 and the mixed dataset in [4]. The results are as follows.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…LERAD-GP is a variation of LERAD, which has been presented by Mahoney et al to find the relation of the attributes in network connections [4]. In the process of experimenting, we found that LERAD-GP outperforms LERAD in detecting attacks from modified data set, in which the simulation artifacts had been removed.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…LERAD [13] used different approaches to tackle different types of data entries. A framework is discovered that uses both normal and anomalous data to find out characteristic features of anomalies on the basis of which anomalies can be removed.…”
Section: I) Statistical Anomaly Detectionmentioning
confidence: 99%
“…Rule Based Mahoney and Chan (2003) present an algorithm for learning rules of normal behavior by mining network data to find precedent consequent pairs of general rules from randomly selected samples. Another approach presented by (Gomez and Dasgupta, 2002) (1) uses genetic algorithms for deriving fuzzy rules for classifying normal and abnormal behavior in networks.…”
Section: Network Security Incidents or Intrusions Reported By Computementioning
confidence: 99%